Why alumni stay engaged with their alma mater? Understanding the factors in Malaysian context - Sium, Mohammed; Prabhakaran, Sudesh; Iqbal, Aatif; Ramachandran, Sridar (Human Resource Management Academic Research Society, 2023)
Alumni engagement is considered one of the key strategies for education institutes to stay competitive and resourceful. Students after graduation can enable their institutes to tap a number of resources through their networks, thus helping with marketing, increasing employability, donations, and mentorship opportunities. Though universities have started capitalizing extensively on alumni as a resource, little is known about the factors influencing alumni engagement in the Malaysian universities context. To address the issue, this study tried to look into the factors affecting alumni engagement by using the School of Business and Economics, Universiti Putra Malaysia as a case study. A quantitative research design was used to collect data from the respondents. The results showed that student experience, external environment, and networking opportunities have a significant and positive effect on alumni engagement. The study has significant theoretical and practical implications and warrants the need for future studies.